Aluminium removal using kenaf core organic cellulose as an additive in newly formulated ultrafiltration flat sheet membrane / Nor Munirah Abdullah - Abdullah, Nor Munirah (2015)
Alum has been extensively used in the coagulation process in water treatment. Potassium alum, which is a hydrated form of potassium aluminium sulphate, is one of the alum categories used as a coagulant agent in water treatment. Today, the permitted baseline level of the aluminium in treated water is 0.2 ppm as declared by the World Health Organization (WHO) and the Ministry of Health (MOH). Membrane is one of the quick fixes to eliminate aluminium concentration in water treatment. Cellulose can be one of the materials used as a polymer or additive for membrane fabrication. Kenaf core has a lot of cellulose and can be a supply source that is viable and lower-priced for membrane fabrication field. Consequently, the objectives of this study were to develop, determine characteristics and evaluate the performance of flat sheet blend UF membranes by using Kenaf core cellulose (KCC) for aluminium removal. The range of flux rate for KCC membrane, 10.29 L/m2.hr was smaller than the synthetic cellulose (SC) membrane, which was 39.13 L/m2.hr with the average pore size of 3.13um for KCC and 3.44um for SC. Hence, the membrane condition of KCC membrane was better than SC membrane. KCC performance test exposes that 69.25% rejection of aluminium documented by KCC5, which was the mid-point of the aluminium removal. To conclude, it was found that the KCC membrane can be used as one of the materials in the membrane field and make the cellulose supply sustainable as well as ecological friendly. Lastly, this study exhibited that KCC5 (Psf 21%: KCC 1%: DMAc 78%) documented the optimum performance as compared to other membranes.